(untitled) (Advancements in Homeopathic Research, 2023)
Introduction: The presence of heavy metals in higher quantity is a cause for concern in herbal medicines. Around 60-70% of homoeopathic medicines are manufactured using herbs. Herbs account for even more than 90% of the frequently used mother tinctures. There is a possibility of heavy metals transfer from herbs to the mother tincture during the manufacturing process. Objective: This study was conducted to find out the transmission of heavy metals from herbs to mother tinctures. Material and methods: 10 herbs have been identified based on the literature survey for the presence of heavy metals (lead, mercury, arsenic and cadmium). Samples of both herbs and the mother tinctures made from them have been studied for the presence of heavy metals in mg/kg. Results & discussion: 8 out of 10 herbs were found to contain heavy metals. However, none of the homoeopathic mother tinctures prepared from these herbs has any trace of the presence of heavy metal. Even though mother tinctures are diluted 10 times and they may contain 1/10th of heavy metals present in the herbs, we could not find even 1/10th of the heavy metal in the mother tincture. This could be due to their insoluble nature in the solvents used. Perhaps all the heavy metals have been retained into the herbal residue. Conclusion: Heavy metals present in the studied herbs do not transport during the manufacturing of homoeopathic mother tinctures. Thus, these homoeopathic mother tinctures may be considered safe with respect to heavy metals.